Personal Values and Job Satisfaction: A Qualitative Perspective on Employee Performance in the Education Sector - Irfan, Mochamad; Al-Hakim, Yusuf Rahman; Sigita, Dwi Sembe (Bulletin of Science, Technology and Society, 2024)
This research aims to explore the influence of personal values on job satisfaction and its impact on employee performance in the education sector. Using a qualitative approach, this research was analyzing the relationship between personal values, job satisfaction, and performance through theoretical perspectives and current literature. The result show that personal values have an important role for improving job satisfaction, especially if they are respected by the organization. High job satisfaction already contributed to improved employee performance through instrinsic motivation and greater commitment to their tasks. Recognition of personal values and organizational support based on good governance are key to creating a productive work environment in the education sector. The research provides a recommends implication for implementation of inclusive policies and the development of merit-based incentive system to improve employee welfare and performance.